Various Forms of Regional Policy Supervision in the Era of Broad Autonomy - PUTERA, Meldy; SISKA; DEWIATI, Yayu; SITOHANG, Erikjon; KRISTHY, Mutia Evi; JOVI; DODDY (Indonesia Strategic Sustainability, 2023)
Purpose: Following abolishing all controlling measures except repressive control, decentralisation triggered fundamental changes in local government administration. Tight control may obstruct regions' autonomy and hamper central-regional relations. Proportional control is indispensable for balancing local governments' freedom. All monitoring measures outside Act 32/2004 are unwarranted without improvement of legal instruments at the central government. Methodology: The method in the given text revolves around the historical analysis and constitutional references to explain the concept of autonomy in the Indonesian regional government system. It highlights the evolution of autonomy from the 1950 Provisional Constitution to the 1945 Constitution amendments, emphasizing the need for autonomy to prevent secessionist tendencies. Findings: Supervision in autonomy serves as a crucial control tool, impacting regional freedom and either fostering autonomy or promoting centralization, contingent on the government system. Historical patterns reveal strict centralization in regional policies, limiting regional autonomy.